Antioxidant Elements Analysis and Enzyme Activities in Hepatocarcinogenesis Induced Rats Treated with Strobilanthes Crispus - Shreeraman, Yogespiriya (2004)
This study was conducted to investigate the effect of 5% (w/v) Strobilanthes crispus crude extract on rat liver during induced hepatocarcinogenesis. Elemental analysis, was done to support this study on all the liver tissues by energy filter transmission electron microscope (EFTEM) and variable pressure scanning electron microscope (VPSEM). Histological and gross changes of liver evaluation were conducted to observe the cellular and morphological changes during induced hepatocarcinogenesis in rats treated with S.crispus. Xenobiotics detoxification enzymes such as aniline hydroxylase (ANH) and glutathione S-transferase (GST) were assayed in liver tissues. Gross examination on liver of rats which were induced with diethylnitrosamine/acetylaminofluorene (DEN/AAF) showed the presence of nodules, haemorrhages and swelling on liver surface. The 5% (w/v) Strobilanthes crispus extract effectively reduced gross changes on liver during induced hepatocarcinogenesis. Meanwhile, histological evaluation revealed that a certain grade of inflammation or necrosis at portal and lobular region and stages of fibrosis during induced hepatocarcinogenesis was successfully reduced after the administration of Strobilanthes crispus extract. Nevertheless, supplementation of S. crispus did not fully recover the liver to normal histological feature. This could be due to the short duration of this experiment. Elemental analysis by VPSEM showed that 5% w/v Strobilanthes crispus extract contained 63.52% of carbon, 16.56% of oxygen, 0.66% of sodium, 0.08% of magnesium, 11.78% of aluminium, 0.17% of phosphorus, 1.19% of sulphur, 1.66% of chloride, 0.95% of potassium, 0.19% of iron, 0.20% of copper, 2.30% of calcium, 0.39% silicon and 0.35% of argentum. The fresh liver tissue obtained from rats administered with DEN/AAF and treated with Strobilanthes crispus extract showed higher percentage distribution of antioxidant elements such as potassium and magnesium when compared to the liver from rats induced with DEN/AAF and untreated rats, DEN/AAF administered and treated with glycyrrhizin rats, normal without treatment rats, normal with Strobilanthes crispus supplemented rats and normal with glycyrrhizin supplemented rats. To detect the antioxidant elements such as potassium, calcium, magnesium and iron at ultrastructural level, EFTEM was used. By utilizing EFTEM, the distributions of these elements were also found to be higher in cancer with S.crispus group compared to other groups. This may suggest showed that tumor cells has high uptake of these elements from S.crispus extract. Meanwhile, DEN/AAF induced rats showed an increase activity of drug/carcinogen detoxification enzymes i.e. GST and ANH. However, 5% w/v S.crispus extract effectively inhibit the activity of these enzymes in DEN/AAF induced rats. S.crispus which is rich with antioxidant elements such as potassium, magnesium, calcium and iron play important role during carcinogenesis. Thus, S.crispus can be considered as potential chemopreventive agent